Effects of three vocabulary learning techniques on vocabulary retention of ESL undergraduates in a Malaysian university - Ali, Zuraina (2012)
This study investigates the effects of three vocabulary learning techniques, which are Contextual Clues, Dictionary Strategy and TMM Vocabulary, in retaining words learnt among ESL learners. Conducting the study serves several purposes. Firstly, it aims at fmding which of the vocabulary learning techniques may result in the highest number of words retained, as measured in the immediate and delayed recall tests. Secondly, it investigates the students' attitudes after they are exposed to the vocabulary learning techniques. Finally, it seeks to find out students' preferences and difficulties of using the techniques in retaining words learnt. The results of the study support Ellis' Model of Second Language Acquisition (SLA) in that instructions need to match L2 learners' aptitude of helping them to retain the words learnt using the vocabulary learning techniques taught to them. Social Constructivist Learning Theory is also used to explain the findings . The theory describes that the construction of knowledge inside the classroom depends on the inter-dependence of social and individual processes. While learners interpret the learning in their own ways, they also need to be dependent on their friends and be facilitated by their teachers in their attempt to retain the vocabulary learnt in class. The study has adopted both quantitative and qualitative methods in collecting its data. A quasi-experiment that tested the effects of retaining vocabulary using Dictionary Strategy, Contextual Clues and TMM Vocabulary involved 123 first-year university students. A survey gauged their attitudes after being exposed to the techniques. Qualitative procedures included the collection of data from interviews, which were conducted to identify both their preferences and the hindrances they encountered in using the techniques. Results from the study showed that there was a significant difference (p = .033 <.05) in Immediate Recall Tests when students were exposed to Dictionary Strategy,Contextual Clues and TMM Vocabulary. The finding for the Delayed Recall Posttest, however, was not supported (p = .735 < .05). There was also evidence that students' attitudes were found to be significant (p = .002 < .05) when they were exposed to the three vocabulary learning techniques. Finally, students' preferences and hindrances relating to the use of the respective vocabulary learning techniques were dependent on the treatments as well as their proficiency levels.